Doxorubicin-conjugated beta-NaYF4:Gd3+/Tb3+ multifunctional, phosphor nanorods: a multimodal, luminescent, magnetic probe for simultaneous optical and magnetic resonance imaging and an excellent pH-triggered anti-cancer drug delivery nanovehicle - Padhye, Preeti; Alam, Aftab; Ghorai, Suvankar; Chattopadhyay, Sarnit; Poddar, Pankaj (Nanoscale, 2015)
Herein, we report the fabrication of a multifunctional nanoprobe based on highly monodispersed, optically and magnetically active, biocompatible, PEI-functionalized, highly crystalline beta-NaYF4:Gd3+/Tb3+ nanorods as an excellent multi-modal optical/magnetic imaging tool and a pH-triggered intracellular drug delivery nanovehicle. The static and dynamic photoluminescence spectroscopy showed the presence of sharp emission peaks, with long lifetimes (similar to 3.5 milliseconds), suitable for optical imaging. The static magnetic susceptibility measurements at room temperature showed a strong paramagnetic signal (chi similar to 3.8 x 10(-5) emu g(-1) Oe(-1)). The nuclear magnetic resonance (NMR) measurements showed fair T-1 relaxivity (r(1) = 1.14 s(-1) mM(-1)) and magnetic resonance imaging gave enhanced T-1-weighted MRI images with increased concentrations of beta-NaYF4:Gd3+/Tb3+ making them suitable for simultaneous magnetic resonance imaging. In addition, an anticancer drug, doxorubicin (DOX) was conjugated to the amine-functionalized beta-NaYF4:Gd3+/Tb3+ nanorods via pH-sensitive hydrazone bond linkages enabling them as a pH-triggered, site-specific drug delivery nanovehicle for DOX release inside tumor cells. A comparison between in vitro DOX release studies undertaken in normal physiological (pH 7.4) and acidic (pH 5.0) environments showed an enhanced DOX dissociation (similar to 80%) at pH 5.0. The multifunctional material was also applied as an optical probe to confirm the conjugation of DOX and to monitor DOX release via a fluorescence resonance energy transfer (FRET) mechanism. The DOX-conjugated beta-NaYF4:Gd3+/Tb3+ nanorods exhibited a cytotoxic effect on MCF-7 breast cancer cells and their uptake by MCF-7 cells was demonstrated using confocal laser scanning microscopy and flow cytometry. The comparative cellular uptakes of free DOX and DOX-conjugated beta-NaYF4:Gd3+/Tb3+ nanorods were studied in tumor microenvironment conditions (pH 6.5) using confocal imaging, which showed an increased uptake of DOX-conjugated beta-NaYF4:Gd3+/Tb3+ nanorods. Thus, DOX-conjugated beta-NaYF4:Get(3+)/Tb3+ nanorods combining pH-triggered drug delivery, efficient luminescence and paramagnetic properties are promising for a potential multifunctional platform for cancer therapy, biodetection, and optical and magnetic resonance imaging.